Relasi Bisnis dan Politik : Studi Peran Keluarga â€œDewi Sriâ€ Dalam Memengaruhi Kebijakan Pemerintah Kabupaten Brebes 2017 â€“ 2022 - Aji, Jerry Abriel Kusuma; Adnan, Muhammad (Journal of Politic and Government Studies, 2020)
Since the election of the Regional Head was held directly, there were many circlesbusinessman or family of entrepreneurs who have joined in enlivening the electoral competitionthe direct. In central Java, Brebes Regency is one of the regions that isThe Regent is from a businessman family. Is the Regent who comes from a familyDoes the entrepreneur cause a conflict of interest? Is the businessman family nottrying to influence policies in the regions that will benefit his business? ResearchThis aims to find out and describe the influence of the family for the Regentcome from a family environment.This research uses descriptive qualitative research method with approachcase study. Researchers obtain research data through primary sources conducted withusing interview and observation methods and secondary data obtained throughcollecting data from documents and report data from related agencies.The results of this study show that the role of the "Dewi Sri" family in influencingBrebes Regency Government policy is no longer dominant. Idza Priyanti's husband is onat the beginning of his leadership period as Regent of Brebes his dominance was very visiblethe policy made by Idza Priyanti does not currently show anyintervention in the policy made. This is because Idza Priyanti has been a long timecoveted by the Corruption Eradication Commission due to many policies madeare collusive and nepotistic that benefit himself or his family. other than thatthe principles of good governance were also carried out in the period of the Idza Priyanti Governmentat present, so practices such as policy interventions are carried out by her husbanditself does not happen again.Keyword: The role of the family "Dewi Sri", Influencing Policy